Period prevalence and cumulative incidence of lamivudine resistance and its associated factor in chronic hepatitis B patient in Hospital Universiti Sains Malaysia (HUSM) - Ismail, Mohd Sharizan (2018)
Background: Lamivudine is an established treatment options for chronic hepatitis B (CHB), however development of viral resistance followed by virological breakthrough made it a less favourable as a first line treatment option. While the alternatives such as entecavir and tenofovir are favoured for first line options due to its higher genetic barrier to resistance, constraints such as financial issue may not make these drugs readily available in some practice. Objectives: The aim of the study is to established period prevalence of lamivudine resistance among patient with CHB who received Lamivudine from January 2010 to Dec 2016, and to explore if there are any factors that associate with development of resistance. The study also aims to look at the response rate for those treated with lamivudine during the same period. Methods This is a retrospective record review done by reviewing record of 41 patients who was or on lamivudine during the period of 2010 to 2016. Subjects are CHB patient who are treated with lamivudine as a first line monotherapy. All relevant data are gathered from the review of case note and recorded in statistical software for analysis. Results Total number of patients included in this study is 41. During the 6 years periods, 9 patients with lamivudine resistance were detected and this yields an overall period prevalence of 21.9%. The cumulative incidence of developing resistance during first year, second year and third year while on lamivudine is 4.9%, 12.2% and 21.9% respectively. Factors such as age, gender, race, pre-treatment viral load, serum ALT, and duration of treatment are shown not associated with development of resistance. In terms of response to treatment, this study shows an overall response rate of 89.5%. Conclusion The prevalence and incidence of lamivudine resistance in this study is lower in comparison with the prevalence and cumulative incidence cited in many literatures. However, further study is warranted to include more patients from other centres in order to improve power of this study, before any recommendation can be proposed.